2011
DOI: 10.1088/0031-8949/84/04/045011
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the squeezing of a two-level system by detuning in non-Markovian environments

Abstract: Squeezing of a two-level atom off-resonantly coupled to a non-Markovian reservoir is investigated. We compared two different definitions of squeezing that are based on the Heisenberg uncertainty relation and the entropy uncertainty relation and found that information entropy squeezing is more precise than variance squeezing as a measure of squeezing. Then we utilized entropy squeezing to examine the influences of the non-Markovian effect and detuning on the atomic squeezing. It is interesting to note that atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Since the entropy squeezing was presented, its properties and schemes for generating entropy squeezing have been widely investigated. Xiao et al [11] have studied the entropy squeezing properties of a two-level atom off-resonantly coupled to a non-Markovian reservoir. Yu et al [12] have obtained the optimal and steady entropy squeezing of a two-level atom in a dissipative cavity under quantum-jump-based feedback and classical field.…”
Section: Introductionmentioning
confidence: 99%
“…Since the entropy squeezing was presented, its properties and schemes for generating entropy squeezing have been widely investigated. Xiao et al [11] have studied the entropy squeezing properties of a two-level atom off-resonantly coupled to a non-Markovian reservoir. Yu et al [12] have obtained the optimal and steady entropy squeezing of a two-level atom in a dissipative cavity under quantum-jump-based feedback and classical field.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, how to maintain and preserve the squeezing of open quantum systems for a long time becomes of great interest. Squeezing of a two-level atom off-resonantly coupled to a non-Markovian reservoir is investigated [17] where atomic squeezing can be protected for a long time with the combined assistance of detuning and non-Markovian effects. By appropriately choosing the atomic motion and the field-mode structure parameters, duration of optimal entropy squeezing can be observed [18].…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, the entropy squeezing (ES) properties of quantum system have been investigated widely. Such as, Yu and Fang have studied the steady and optimal entropy squeezing of a two-level atom with quantum-jump-based feedback and classical driving in a dissipative cavity and provided a scheme of generating steady and optimal entropy squeezing in the two-level system; [3] Wang has investigated sustained optimal entropy squeezing of a two-level atom via non-Hermitian operation and provided a scheme for generating the sustained optimal entropy squeezing of the atom via non-Hermitian operation; [4] Xiao has studied the entropy squeezing of a two-level system by detuning in non-Markovian environments and shown that the atomic entropic squeezing can be protected for a long time when both the non-Markovian effect and detuning are present simultaneously; [5] the entropy squeezing of a two-level atom in Jaynes-Commings model has been reported widely; [6] Zou has studied the quantum entropic uncertainty relation and entanglement witness in the two-atom system coupling with the non-Markovian environments. [7,8] However, these results are obtained only in the case of two-level atom, the entropy squeezing properties of three-level atom have not yet been involved until now.…”
Section: Introductionmentioning
confidence: 99%